2011
DOI: 10.1097/mao.0b013e3181f7aba3
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Steroid Therapy for Sudden Hearing Loss

Abstract: On the basis of the available literature, it seems that topical steroids can be a valuable solution for ISSNHL patients who either cannot tolerate systemic steroid therapy or are refractory to it. Concerning the combined therapy, due to the controversial results of the existing studies, it cannot be determined yet whether this treatment protocol could yield superior results as a first line therapy. The need for establishment of standard criteria of hearing recovery should be underlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 43 publications
1
73
0
3
Order By: Relevance
“…This complication, however, is rare and frequently resolves spontaneously or with a paper patch myringoplasty in the office. Existing studies showed considerable variability in the dose and concentration of steroids administered, the timing, frequency, and total number of injections (ranging from one to several to continuous); and drug selection (dexamethasone and methylprednisolone) [18]. This high degree of variability makes it difficult to compare the results across studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This complication, however, is rare and frequently resolves spontaneously or with a paper patch myringoplasty in the office. Existing studies showed considerable variability in the dose and concentration of steroids administered, the timing, frequency, and total number of injections (ranging from one to several to continuous); and drug selection (dexamethasone and methylprednisolone) [18]. This high degree of variability makes it difficult to compare the results across studies.…”
Section: Discussionmentioning
confidence: 97%
“…Their protocol consisted of early injections for 3 consecutive days, with only 3 of 34 patients failing to improve. A systematic review concluded that IT steroids can be a valuable solution for patients with ISSNHL who either cannot tolerate systemic steroid therapy or are refractory to it [18]. For patients with diabetes who cannot take systemic corticosteroids, IT steroids may be an alternative [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of this treatment, which is called intratympanic steroid treatment (ITS) in the literature, has been reported in many studies (13,14). However, the timing of this therapy is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…1 It commonly presents as acute hearing loss occurring within 72 hours and is an emergency condition requiring immediate medical attention. Sudden sensorineural hearing loss (SSNHL) is defined as a hearing loss of 30 dB or more in one ear or both over at least three contiguous frequencies in audiometry, over a period of 72 hours or less.…”
Section: Introductionmentioning
confidence: 99%